Effects of Rhythm and Rate-Controlling Drugs in Patients With Permanent His-Bundle Pacing - Su, Lan; Xia, Xue; Liang, Dongjie; Wu, Shengjie; Xu, Lei; Xu, Tiancheng; Wang, Songjie; Chen, Xiao; Huang, Weijian (Frontiers in Cardiovascular Medicine, 2020)
Introduction: Antiarrhythmic drug therapy can affect pacemaker parameters in both the atrial and ventricular myocardium. It is not known whether antiarrhythmic drugs impact His bundle pacing/sensing parameters and His to ventricle (H-V) intervals following permanent His bundle pacing (HBP). The aims of the study were to prospectively determine the influence of rhythm and rate-controlling drugs on pacing parameters and H-V conduction after His bundle lead implantation and to assess the impact of rhythm and rate-controlling drugs on the safety of HBP. Materials and Methods: Patients (N=140) with QRS duration < 120ms who met permanent pacing indications were prospectively enrolled. Propafenone, lidocaine and adenosine were injected intravenously after implantation of 3830 lead during the procedure. Metoprolol succinate, amiodarone and digoxin were taken orally for one month. Pacing parameters before and after drug intervention was measured, including His capture threshold, sensing and impedance, H-V interval and conduction. Results: There were no statistically significant differences in His bundle pacing thresholds, impedance and sensing after drug intervention at implantation or during two-month follow-up (P > 0.05). The HV interval was not affected except in the large-dose propafenone group where HV interval prolonged (P=0.001). All patients maintained 1:1 H-V conduction following drug administration. Conclusion: There was no adverse impact on the HBP parameters or H-V conduction after the administration of commonly used dosage of rhythm and rate-controlling drugs. The drugs were safe in patients with permanent His bundle pacing.